Analysis of the Influence of Knowledge Management on Sustainability Practices (Tourism Village Communication Forum of Sleman Regency) - Rahmaningtyas, Fadila; Hadi, Syamsul; Subiyanto, Didik (Dinasti International Journal of Economics, Finance & Accounting, 2024)
The objective of the present research was to examine the effects of Knowledge Management on Sustainability Practices in the communication forum of the Tourism Village Development of Sleman regency. In this study, a quantitative approach with survey design was used to obtain data from 80 members of the forum using a questionnaire. The data was analyzed using SPSS version 22.0 to check for validity and reliability, while examination of the structural model was done using SEM-PLS software. The analysis shows that in the initial test of the effect of Knowledge Management on Sustainability Practices, the coefficient was 0.461, the t-statistic was 3.599, and the p-value was 0.000, which is statistically significant. Hence, Knowledge Management has been found to be positively contributing towards the improvement of Sustainability Practices in the forum. Effective knowledge management enables managers of tourism villages to respond to environmental challenges, implement sustainable practices successfully, and enhance the well-being of the community.